Integration of Customary Law in Agrarian Law Development in the Industrial Revolution 4.0 Era: Significance and Urgency - Erdika, Lucy; Brahmana, Sindy Sri Widyawati Sembiring; Herlindah; Permadi, Iwan (Peradaban Journal of Law and Society, 2024)
The Industrial Revolution 4.0 era recently offers automation systems across various aspects of life. This situation challenges Indonesia's land law rooted in customary law. This article aims to explore the role and relevance of customary law as the foundation of national agrarian law in the face of rapid Industry 4.0 growth. The findings indicate that customary law, as the cornerstone of the Basic Agrarian Law, is crucial not only as a source of norms and supplementary norms in national land law. Recognition of customary law remains pivotal to ensure the sustainability of indigenous communities, protect traditional land rights, and promote inclusive agrarian justice. The integration of customary law within Indonesia's national legal framework reflects a commitment to advancing agrarian justice and supporting the principles of the Unitary State of the Republic of Indonesia. Thus, customary law continues to be relevant as a foundation and principle for legislative formation, including agrarian law. A legal pluralism system recognizing customary law as an integral part of agrarian law holds significant potential in supporting comprehensive and inclusive agrarian justice in Indonesia, aligning with agrarian law policies aimed at safeguarding pluralistic rights of indigenous communities. Revolusi Industri 4.0 baru-baru ini menawarkan sistem otomatisasi dalam berbagai bidang kehidupan. Situasi ini menantang hukum tanah Indonesia yang berasal dari hukum adat. Artikel ini bertujuan untuk mengetahui peran dan relevansi hukum adat sebagai dasar dari hukum agraria nasional dalam menghadapi pertumbuhan pesat Revolusi Industri 4.0. Hasil kajian menunjukkan bahwa hukum adat sebagai fondasi dari Undang-Undang Pokok Agraria tidak hanya penting sebagai sumber norma dan norma pelengkap dalam hukum tanah nasional. Pengakuan terhadap hukum adat tetap krusial untuk memastikan keberlanjutan komunitas adat, perlindungan hak-hak tanah tradisional, serta promosi keadilan agraria yang inklusif. Integrasi hukum adat dalam kerangka hukum nasional Indonesia mencerminkan komitmen untuk memajukan keadilan agraria dan mendukung prinsip Negara Kesatuan Republik Indonesia. Dengan demikian hukum adat masih dan akan terus relevan sebagai dasar dan prinsip untuk pembentukan peraturan perundang-undangan, termasuk hukum agraria. Sistem pluralisme hukum yang mengakui hukum adat sebagai bagian integral dari sistem hukum agraria menjadi potensi besar dalam mendukung keadilan agraria yang menyeluruh dan inklusif di Indonesia, sejalan dengan arah kebijakan hukum agraria yang bertujuan melindungi hak-hak pluralis masyarakat adat.